Pendampingan dalam Implementasi Standar Operasional Prosedur (SOP) dan Program Accurate dalam Pencatatan Penjualan kepada Karyawan CV. Duta Survey Indonesia - Wulan, Wanda Sofiatul Fauziah Sih; Ashari, Muhammad Hasyim (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The aim of this service activity is to increase the efficiency of sales administration at CV. Indonesian Survey Ambassador by implementing standard operating procedures (SOP) and accurate programs. The method used in this service is direct assistance to company employees in implementing SOPs and using the Accurate Program to record sales. Data analysis shows that many companies, including CV. Duta Survey Indonesia, experienced difficulties in managing sales administration due to a lack of clear SOPs and the use of an inefficient recording system. With the assistance provided, company employees are able to understand and implement SOPs well and utilize the Accurate Program to record sales effectively. In conclusion, this service activity succeeded in providing useful guidance for similar companies in considering the implementation of SOPs and similar sales management programs to improve operational efficiency and overall sales performance.